(untitled) (Nepal Agriculture Research Journal, 2009)
An experiment was conducted in Institute of Agriculture and Animal Science, Rampur, Chitwan during 2003 to find out the effect of harvesting method and calcium chloride treatment on postharvest physiology of tomato. Tomato (Hybrid Gootya) fruits with stalk and without stalk were harvested at breaker stage and dipped in distilled water and different concentrations of calcium chloride viz. 0.25%, 0.50%, 0.75% and 1% for fifteen minutes. Fruit were then air-dried and stored at ambient condition (24 ± 3°C and 70 ± 5 % RH). Among the tested treatments the least cumulative physiological weight loss (12.14%) was exhibited by 1% calcium chloride. The shelf life of tomato fruits was significantly affected by harvesting method and calcium treatment. Tomato fruit harvested with stalk had higher shelf-life (15 days) as compared to those harvested without stalk (12.93 days) irrespective to calcium chloride application. The maximum shelf life was noticed in 1% calcium chloride treated fruits (16.50 days) followed by 0.75% calcium chloride treated fruits (16.17 days). Key words: Calcium chloride; physiological weight loss; shell life; tomato DOI: 10.3126/narj.v7i0.1864 Nepal Agriculture Research Journal Vol.7 2006 pp.37-41